Investment Potential of the Manufacturing Industry - N. M. Abdikeev; Yu. S. Bogachev; S. R. Bekulova (Финансы: теория и практика, 2019)
The article considers investment in fixed assets of the manufacturing industry as one of the main factors of its development. The manufacturing industry is shown to be the growth driver of national economy for developed and developing countries. The analysis of exports and imports of the first 15 countries in the ranking in terms of gross domestic product calculated at purchasing power parity (GDP at PPP) shows the leading role of the manufacturing industry in the global economy. At the same time, competitiveness in the global market is determined by high-tech products. Therefore, for the sustainable development of the Russian economy, it is necessary to create investment conditions for the advanced development of high-tech segments of the manufacturing industry. However, the current structure of investments in fixed assets contributes to the development of such services sector segments as “Transportation and storage”, “Real estate operations”. In the structure of investments in fixed assets, the largest share belongs to investments in buildings and structures, and intellectual property items account for no more than 10%. It is shown that the lack of investment resources is the main reason for the reduction (by 1.5 times) of the contribution to the value added of the manufacturing industry in Russia, production of machinery and equipment. This leads to an increase in dependence on imports, a fall in the share of products from high-tech sectors. To analyze the development potential of manufacturing industries, the authors introduced an indicator of investment intensity per 100 rubles of shipped industrial products. It was determined that enterprises with a joint Russian and foreign form of ownership lead in terms of investment intensity. At the same time, private enterprises, leading in terms of output, demonstrate weak investment activity. The low investment attractiveness of high-tech manufacturing sectors is shown. The regional structure of the manufacturing industry was analyzed. There is a high level of regional concentration of the manufacturing industry in Russia. At the same time, the authors show its relatively weak significance in the structure of the gross regional product in the majority of the constituent entities of the Russian Federation. It has been proposed to develop a program at the federal level for the advanced development of production in the high-tech and medium-technology high-level sectors for 10–15 years. It is proposed to create a supradepartmental executive authority to manage this program.